(3EQTGO GdMjGQi aj eYQaI ESJNQGL YjO GdfUGQis - (3NVQ Hf YHO GdbGOQ GdHQdSj GdHQjTj GdbHGfjs
(3ChdgG (B:s
(3GdMeO ddg GdPi fhQ bdhH YdeGFg HGdYde hGdGjeGf deG MUd GdNda Hjf WGFaI GdfUGQi GdjYbhHjI hHjf GHfGA LfSge ef Hfi GdfUQGfjI Ydi GUhd Uhege GdcHjQ aWdH efi MSGH Pdc dchf Gfg eQJH Ydi GUhd GdbGYOI s
(3BNQgG (B:s
(3hdG jecf Gf jchf Ghdg GMO gPg GdKdGKI GjGe ChdgG jhe GdGKfjf hGdGQHYGA hGdLeYG hjecf Gf jchf Ghdg GdGMO hGdKdGK heG jbGHd GdYOO GdeWdhH JMJ GdaSM GdaQVi gh GdaSM GdeSjMi Je s
(3GdfSNI HgG MhGTs
(3HChdg hBNQg fbhd eNJdaIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3HGQjS s
Keywords: (3Gdadcs